Data-Driven Analysis of Causes and Risk Assessment of Marine Container Losses: Development of a Predictive Model Using Machine Learning and Statistical Approaches - Myung-Su Yi; Byung-Keun Lee; Joo-Shin Park (Journal of Marine Science and Engineering)
This study presents a comprehensive, data-driven analysis of the causes and risks associated with container loss during maritime transport, utilizing incident data from 2011 to 2023. By employing advanced statistical analysis, machine-learning techniques, and data preprocessing, the study identifies key factors influencing container loss, including vessel size, incident locations, and primary causes. A predictive model based on decision trees was developed to assess the severity of container loss incidents, while K-means clustering was used to classify incident zones. Adverse weather conditions were found to be the predominant cause, accounting for 57.14% of incidents. The study reveals that larger vessels, despite experiencing fewer incidents, face more severe losses, whereas smaller vessels are more prone to frequent but less severe losses. The decision-tree model demonstrated high accuracy in predicting low-risk incidents but showed limitations in moderate- and high-risk scenarios. The findings underscore the importance of understanding the correlation between vessel parameters and incident outcomes to enhance risk management strategies. The study also highlights the potential for improving predictive capabilities by incorporating environmental data. These insights provide a robust framework for ship owners and maritime authorities to anticipate and mitigate risks, emphasizing the need for continuous monitoring and enhanced safety measures in maritime operations.